2016
DOI: 10.1111/and.12609
|View full text |Cite
|
Sign up to set email alerts
|

Testicular versus ejaculated spermatozoa in ICSI cycles of normozoospermic men with high sperm DNA fragmentation and previous ART failures

Abstract: As a part of male assessment, conventional sperm parameters including morphologic features have been dedicated as major factors influencing fertilisation and pregnancy rates in assisted reproductive technology (ART). Genomic integrity of spermatozoa has also been found to influence fertility prognosis, and hence, sperm DNA fragmentation index (DFI) has been adopted by many centres to document this entity. Despite several suggested approaches, there is lack of universal consensus on optimising fertility outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 39 publications
0
53
0
1
Order By: Relevance
“…The authors also found that SDF assessed by the SCD method was 5-fold lower in testicular sperm than in ejaculated sperm (40.7%±9.9% vs. 8.3%±5.3%; P<0.001). In another study of similar design but involving normozoospermic men with high SDF, the fertilization rate and miscarriage rate did not differ; however, a significantly higher pregnancy rate was reported in testicular sperm cycles (85). …”
Section: Indications For Sdf Testingmentioning
confidence: 84%
“…The authors also found that SDF assessed by the SCD method was 5-fold lower in testicular sperm than in ejaculated sperm (40.7%±9.9% vs. 8.3%±5.3%; P<0.001). In another study of similar design but involving normozoospermic men with high SDF, the fertilization rate and miscarriage rate did not differ; however, a significantly higher pregnancy rate was reported in testicular sperm cycles (85). …”
Section: Indications For Sdf Testingmentioning
confidence: 84%
“…Four studies (32,34,36,45) provided fertilization data for 3,840 oocytes injected with either testicular sperm or ejaculated sperm in high-SDF patients. The mean twopronuclei fertilization rates with the use of Testi-ICSI and Ejac-ICSI were 59.8% and 68.7% (P< .001), respectively.…”
Section: Fertilization Ratesmentioning
confidence: 99%
“…However, some authors showed conflicting results about the issue. 16 In this study, almost 2/3 of viable pregnancies happened in women who had more than eight oocytes retrieved. According to some authors, 17 the live births rate significantly increases with the number of retrieved oocytes.…”
Section: Discussionmentioning
confidence: 63%